2021
DOI: 10.1093/femsec/fiab157
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous microbial communities in heavy oil show a threshold response to salinity

Abstract: Microbial degradation influences the quality of oil resources. The environmental factors that shape the composition of oil microbial communities are largely unknown because most samples from oil fields are impacted by anthropogenic oil production, perturbing the native ecosystem with exogenous fluids and microorganisms. We investigated the relationship between formation water geochemistry and microbial community composition in undisturbed oil samples. We isolated 43 microliter-sized water droplets naturally en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The fact that the relative abundances of the core taxa were variable may have resulted from variable selection due to small-scale environmental heterogeneity or due to biotic interactions. In a recent analysis of 43 water droplets from the Pitch Lake we found that 20.4% of the variability in community composition could be explained by local differences in the concentrations of chloride, sulfate, and potassium (Voskuhl et al 2021 ). The so far unexplained 79.6% of the variability may have been caused by local differences of other, unmeasured environmental variables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The fact that the relative abundances of the core taxa were variable may have resulted from variable selection due to small-scale environmental heterogeneity or due to biotic interactions. In a recent analysis of 43 water droplets from the Pitch Lake we found that 20.4% of the variability in community composition could be explained by local differences in the concentrations of chloride, sulfate, and potassium (Voskuhl et al 2021 ). The so far unexplained 79.6% of the variability may have been caused by local differences of other, unmeasured environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for oil and water droplet sampling, DNA-extraction and 16S rRNA gene library preparation have been described previously (Pannekens et al 2020 , Voskuhl et al 2021 ). In short, oil was sampled from different locations on the Pitch Lake surface in Trinidad and Tobago in February 2017 and March 2018 and 2019 using sterile equipment, and shipped to Germany under nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at least according to older studies, gas exchange between water and atmosphere is not affected by oil slicks (Kinsey, 1973). Lowered salinity as caused by reduced evaporation might play an important role for microbial communities in oil slicks because microbial communities for instance in oil reservoirs have been observed to respond threshold-dependent to salinity, resulting in abrupt changes to less diverse and uneven communities (Shelton et al, 2016;Voskuhl et al, 2021).…”
Section: Comparison Of Natural and Oil Slick Featuresmentioning
confidence: 99%